349 INTRAVENOUS CANGRELOR INFUSION IN PATIENTS UNDERGOING COMPLEX VERSUS NON-COMPLEX PERCUTANEOUS CORONARY INTERVENTION: A SUBANALYSIS OF THE ICARUS REGISTRY. (15th December 2022) - Gragnano, Felice; Benenati, Stefano; Scalamera, Riccardo; Bertero, Edoardo; Capolongo, Antonio; De Sio, Vincenzo; Musumeci, Giuseppe; Annibali, Gianmarco; Campagnuolo, Salvatore; Galasso, Gennaro; Silverio, Angelo; Bellino, Michele; et al.
Abstract: Aims: To compare the clinical characteristics and in-hospital outcomes of patients undergoing complex vs. non-complex percutaneous coronary intervention (PCI) with peri-procedural use of cangrelor. Methods: Consecutive patients treated with cangrelor in 6 Italian institutions were retrospectively enrolled in the ICARUS ("Intravenous CAngrelor in high-bleeding Risk patients Undergoing percutaneouS coronary intervention", NCT05505591) registry. Complex PCI was defined as any of the following: 3 vessels treated, ≥3 stents implanted, ≥3 lesions treated, bifurcation with 2 stents implanted, total stent length >60 mm, or chronic total occlusion. The primary endpoint was net adverse clinical events (NACE), defined as a composite of cardiovascular death, myocardial infarction, stroke, definite or probable stent thrombosis and Bleeding Academic Research Consortium (BARC) 2, 3 or 5 bleeding, at 48 hours. Secondary endpoints were assessed at 48 hours and throughout the hospital stay. Results: Among 551 patients enrolled in the ICARUS registry and undergoing PCI between January 2019 and August 2022, a total of 534 (97%) patients had complete information on PCI complexity, of whom 173 (32%) underwent complex PCI and 361 (68%) underwent non-complex PCI. In general, patients with complex PCI had similar clinical features compared with non-complex PCI patients, including comparable prevalence of high bleeding risk (HBR) status according to the ARC-HBR definition (35% vs. 30%, p=0.253), but complex PCI patients presented more often with cardiogenic shock (9% vs. 2%, p<0.001). PCI with ≥3 stents implanted was the most frequent criterion of procedural complexity (62%). The incidence of the primary endpoint of 48-hour NACE (10% vs. 7%, p=0.264) and other clinical endpoints occurring at 48 hours or during hospitalization did not differ between complex and non-complex PCI patients. Conclusions: Among patients receiving peri-procedural cangrelor, about 30% of cases underwent complex interventions. Notwithstanding higher procedural complexity, short-term clinical outcomes were similar between complex and non-complex PCI patients.